A new insight on the effects of Schiff Base Iron (III) complexes in breast cancer cells for clinical radiotherapy - Talik Sisin, Noor Nabilah; Ab Rashid, Raizulnasuha; Abdullah, Reduan; Abdullah, Arifah Nazirah; Dollah, Norhayati; Algethami, Merfat; Assran, Awatef S.; Mohamed, Faizal; Rahman, Wan Nordiana (Elsevier, 2024)
Purpose: Breast cancer is a significant global health concern, and researchers strive to enhance radiotherapy outcomes while minimizing the side effects. Schiff Base Iron (III) Complexes are one of the prospective elements that can be used as radiosensitizer or radioprotective agents in cancer radiotherapy. This study investigates the potential effects of Schiff base (ligand 2; L2) with Fe(III) in MCF-7 breast cancer cells under clinical radiotherapy treatment. Methods: The effects of the Schiff Base Iron (III) Complexes were measured using clonogenic assay with MCF-7 breast cancer cells. The cells were irradiated with megavoltage 6 MV photon, 6 MeV electron and high dose rate (HDR) brachytherapy with 192Ir source at different doses. Intercellular localization of Fe(III)-L2 complexes and antioxidant activities were also investigated. Results: The Fe(III)-L2 complexes were observed to be internalized by cellular nuclei without any effects on the cells. Interestingly, the Fe(III)-L2 complexes indicate radioprotective effects which provide intriguing insight towards application of metal ions complexes as radioprotector in cancer radiotherapy. The Fe(III)-L2 complexes also exhibit scavenging activities of free radical which further proved the antioxidative properties and radioprotective effects. Conclusion: The Fe(III)-L2 complexes show the radioprotective effects and antioxidant properties in MCF-7 cells, particularly for HDR brachytherapy. The findings suggest potential applications of the Fe(III)-L2 complexes as radioprotector agents in clinical radiotherapy.